The evolving hematopoietic niche during development - Sánchez-Lanzas, Raúl; Jiménez-Pompa, Amanda; Ganuza, Miguel (Frontiers in Molecular Biosciences, 2024)
Mammalian hematopoietic stem cells (HSCs) emerge from the hemogenic endothelium in the major embryonic arteries. HSCs undergo a complex journey first migrating to the fetal liver (FL) and from there to the fetal bone marrow (FBM), where they mostly remain during adult life. In this process, a pool of adult HSCs is produced, which sustains lifelong hematopoiesis. Multiple cellular components support HSC maturation and expansion and modulate their response to environmental and developmental cues. While the adult HSC niche has been extensively studied over the last two decades, the niches present in the major embryonic arteries, FL, FBM and perinatal bone marrow (BM) are poorly described.Recent investigations highlight important differences among FL, FBM and adult BM niches and emphasize the important role that inflammation, microbiota and hormonal factors play regulating HSCs and their niches. We provide a review on our current understanding of these important cellular microenvironments across ontogeny. We mainly focused on mice, as the most widely used research model, and, when possible, include relevant insights from other vertebrates including birds, zebrafish, and human. Developing a comprehensive picture on these processes is critical to understand the earliest origins of childhood leukemia and to achieve multiple goals in regenerative medicine, such as mimicking HSC development in vitro to produce HSCs for broad transplantation purposes in leukemia, following chemotherapy, bone marrow failure, and in HSC-based gene therapy.